REGISTRATION AND ADMINISTRATION SYSTEM IN DENTAL CLINICSM PANTI NUGERAHA USING VISUAL BASIC 6.0 - Prita Prigati Dili Astanti; Rahayu Noveandini, Skom, MM (Jurnal Sistem Informasi, 2007)
Scientific writing is aimed to know the registration and administration of thetreatment of patients with a way of making the report manually become computerizedpreparation of reports specially programmed with Visual Basic 6.0. This is ascientific research is research with how to obtain data or report results regitrasi andpatient administration. The author obtained these data by conducting interviews withthe Head of Unit (Director) clinics, studying books and literature. From this researchwe can conclude that by using computerized will gain the convenience and assist theprocess of registration and administration system of treatment of patients, thusproviding a fast and accurate information.